2001
DOI: 10.1302/0301-620x.83b4.0830513
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of arthroscopic partial lateral meniscectomy in knees without associated damage

Abstract: We evaluated the outcome of partial lateral meniscectomy of 31 knees in 29 patients whose knees were otherwise normal. The mean follow-up was 10.3 years. According to the Lysholm score, 14 knees were rated as excellent, four as good, five as fair and eight as poor, with a mean score of 80.5 points. Radiologically, only one lateral compartment was classified as grade 0, eight as grade 1, nine as grade 2, 11 as grade 3, and two as grade 4 according to Tapper and Hoover. No significant (p < 0.05) correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 0 publications
2
51
0
1
Order By: Relevance
“…For this reason, partial meniscectomy has historically been the mainstay of surgical treatment for normal meniscal tears. Despite the benefits of short-term pain relief, partial meniscectomy has been associated with a substantially increased incidence of progressive degenerative changes [18][19][20][21][22][23][24][25][26][27] . This finding has emphasized the importance of meniscal preservation whenever feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, partial meniscectomy has historically been the mainstay of surgical treatment for normal meniscal tears. Despite the benefits of short-term pain relief, partial meniscectomy has been associated with a substantially increased incidence of progressive degenerative changes [18][19][20][21][22][23][24][25][26][27] . This finding has emphasized the importance of meniscal preservation whenever feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, degenerative changes associated with meniscectomies have been linked to increased joint contact stress (hereafter referred to as contact pressure) in the adjacent articular cartilage as measured in vitro [18][19][20][21][22][23][24][25][26][27] . To date, however, experimental models have been primarily conducted under static or quasi-static uniaxial loading conditions 8,[28][29][30][31][32][33] .…”
mentioning
confidence: 99%
“…A summary score ranging from 0 to 100 points is generated, with a higher score reflecting better knee function. The Tegner-Lysholm rating scale is the most widely used patient-reported outcome instrument in orthopaedic research [6,8,15,17,22] and is acceptable, reliable, and valid [10]. Knee function was assessed preoperatively to provide a baseline knee function score.…”
Section: Methodsmentioning
confidence: 99%
“…It is the most widely used patient-reported knee function outcome instrument in orthopaedic research [29][30][31][32] and has demonstrated reliability and validity 33 . Items are differentially weighted on the basis of clinical criteria, and a summary score ranging from 0 to 100 points is obtained, with a higher score reflecting better knee functioning.…”
Section: Primary Outcome Measurementioning
confidence: 99%